Comparison of the differences in iron and anemia-related markers by ultramarathon distance - Shin, K.-A.; Kim, Y.-J. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Iron and anemia-related markers in long-distance runners have mostly been investigated following single distance marathons, with contradictory findings. This study compared iron and anemia-related markers according to marathon distance. METHODS: Iron and anemia-related markers were analyzed from blood samples of healthy, adult male (aged =40-60 years) long-distance runners before and after ultramarathon races of 100 km (N.=14), 308 km (N.=14), and 622 km (N.=10). Fe, total iron-binding capacity (TIBC), unsaturated iron-binding capacity (UIBC), transferrin saturation, ferritin, high-sensitivity C-reactive protein (hs-CRP), white blood cell (WBC), red blood cell (RBC), hemoglobin (Hb), and hematocrit (Hct) levels were analyzed. RESULTS: On completion of all races, the iron levels and transferrin saturation decreased (P<0.05), while the ferritin and hs-CRP levels and WBC counts significantly increased (P<0.05). The Hb concentrations increased after the 100-km race (P<0.05), although the Hb levels and Hct decreased after the 308- and 622-km races (P<0.05). The highest-to-lowest levels of unsaturated iron-binding capacity were found following the 100-km, 622-km, and 308-km races, whereas those of the RBC count were found following the 622-km, 100-km, and 308-km races. Ferritin levels were significantly higher following the 308-km race than after the 100-km race (P<0.05); hs-CRP levels in the 308- and 622-km races were higher than those in the 100-km race. CONCLUSIONS: Ferritin levels increased due to inflammation following distance races, and runners experienced transient iron deficiency without anemia. However, the differences in iron and anemia-related markers according to the ultramarathon distance remain unclear.